Analysis of Consumer Preference Towards Buying Interest Lactasari Milk in Grobogan Regency - Atmojiwa, Raya Kandela; Mariyono , Joko; Handayani, Migie (Jurnal AGRISEP, 2026)
Lactasari milk took advantage of opportunities by producing a variety of quality milk products to meet the growing demand and preferences of consumers in Grobogan Regency. This study aimed to examine consumer characteristics, how the number family members affects the amount of Lactasari milk purchased, and consumer preferences for Lactasari milk in Grobogan Regency. The research took place from November to December 2024 at Purwodadi Market, Nglejok Market, Panti Rahayu Yakkum Hospital, and Purwodadi Hospital. The method involved a survey with questionnaires and non-probability sampling through accidental sampling. A total of 100 respondents who bought Lactasari milk participated. The analysis included descriptive analysis, crosstab analysis, and chi-square analysis to examine the link between the number of family members and the amount of Lactasari milk purchased. Conjoint analysis identified which features of Lactasari milk affected consumer preferences.The results showed that the average age of consumers was 41 years or older. Most buyers were female, many had a Diploma III/IV or Bachelor’s degree, the most common number of family members was four, and most consumers had a monthly income of IDR 2,500,000.00 or more. Crosstab and chi-square analyses revealed a significant link between the number of family members and the amount of Lactasari milk purchased. The conjoint analysis showed that consumers preferred Lactasari milk that was affordably priced, had a chocolate flavor, came in large size (1,000 ml), and was packaged in plastic pillow. According to importance values, price was the most important attribute, followed by size, taste, and packaging.